Peluang Pengembangan Harmonisasi Halal: Studi Literatur - Hamzah Robbani (Neolectura, 2021)
This study aims to examine the literature related to halal, especially how halal is in Indonesia. This study uses qualitative methods with literature study analysis techniques. Researchers use a basic research approach to raise halal issues that can become opportunities and threats for the development of the halal sector. The researcher applies a systematic literature review (SLR). the result Halal issues are widely discussed in research both at home and abroad. Researchers used Emerald as the primary reference source and developed a meta-analysis protocol by structuring the literature as follows Global Halal Industry Halal Certification, Centralization halal hub, Halal certification, Halal Harmonization, Level of knowledge, Halal Tourism, Halal Food, Halal Cargo, Halal during Pandemic Covid -19